Viable Molecular Hybrids of Bacteriophage Lambda and Eukaryotic DNA - Thomas, Marjorie (1974)
A bacteriophage λ strain has been constructed and a method developed by which DNA from potentially any source can be covalently inserted through EcoRI cohesive ends into the middle of the λ DNA. These hybrid DNAs can infect nonrestricting Escherichia coli cells and can then propagate as plaque-forming phage. A unique feature of this λ strain is that extra DNA in the middle of its genome is required for plaque formation. A large number of such phages have been produced with E. coli DNA and Drosophila melanogaster DNA.